Stereotyped topography of different elevated contingent negative variation components in children with migraine without aura points towards a subcortical dysfunction - Bender, Stephan; Weisbrod, Matthias; Resch, Franz; Oelkers-Ax, Rieke (Pain, 2007)
Increased negativity during contingent negative variation (CNV) is thought to reflect abnormal neural activation in adult migraineurs’ attention related processing. Findings in childhood and adolescence have yielded less clear results. This study characterizes the age-dependent development of CNV topography in migraine during childhood in order to elucidate the origin and cerebral generators of described CNV elevations. A large sample of children with primary headache (migraine with/without aura, tension type headache) and healthy controls aged 6-18 years was examined in a CNV paradigm using 64-channel high resolution DC-EEG. Patients were tested for diagnose-related topographic group differences of initial CNV (iCNV), late CNV (lCNV) and postimperative negative variation (PINV). All three CNV components of 6-11-year-old migraineurs without aura showed elevated negativity over the supplementary motor area (SMA) and around the vertex. Migraine children lacked age-dependent development of late CNV around Cz as previously reported. However, they showed a normal development of late CNV over pre-/primary motor cortex (MI). There was no marked elevation of iCNV amplitude over frontal areas (orienting reaction) nor specific amplitude elevations over “motor” or “sensory” areas during sustained attention (late CNV). Additional “pre-mature” activation e.g., in the locus coeruleus (leading to diffuse cortical activation summing up to a maximum over the vertex) or the basal ganglia (interacting with SMA) explained the rather stereotyped CNV elevation around the vertex better than a specific implication of the cortical systems responsible for orienting, motor preparation or sensory attention.